A revision of the French Trichobranchidae (Polychaeta), with descriptions of nine new species - Lavesque, Nicolas; Hutchings, Pat; Daffe, Gullemine; Nygren, Arne; Londoño-Mesa, Mario H. (Zootaxa, 2019)
Trichobranchidae from French waters are revised based on material available in French marine stations and newly collected specimens. This research is the first part of the “Spaghetti Project” aiming to revise French species of terebellids and trichobranchids. It confirms the absence of the so-called cosmopolitan species Terebellides stroemii from French waters, and describes eight new species of Terebellides: T. bonifi n. sp., T. ceneresi n. sp., T. europaea n. sp., T. gentili n. sp., T. gralli n. sp., T. lilasae n. sp., T. parapari n. sp. and T. resomari n. sp. and one species of Trichobranchus: T. demontaudouini n. sp. using both morphological and molecular tools. An identification key for all European species of Trichobranchidae is provided.